The degree to which high school administrators manage the educational crisis in Ajloun province under the Corona pandemic from the point of view of teachers - Momani, Alaa Kamal Sami (Journal of Educational and Psychological Sciences, 2022)
The purpose of the study was to determine the degree to which secondary school administrators practiced managing the educational crisis in Ajloun province under the Corona pandemic from the point of view of teachers. The researcher used the analytical descriptive curriculum, using the resolution study tool distributed to a group of school teachers in Ajloun province. (93) Teachers selected in a simple, random manner. The study found the following findings. The results of the study showed the degree to which high school administrators practiced to manage the educational crisis in Ajloun province in the Corona pandemic, from the point of view of teachers. 3.411 That is, the degree of consent readiness (average), and the absence of statistically significant differences between the computational averages of the responses of sample members to the tool as a whole attributable to variables (gender, experience), In the light of the findings, the researcher recommended that all schools should be equipped with the appropriate tools, tools and various equipment to help manage and respond to the crisis in a more effective manner, and that appropriate channels of communication and communication should be put in place between the components of the educational process and the various departments in order to respond to and manage crises effectively and with high capacity.